Proceedings of the 2014 Annual Conference on Genetic and Evolutionary Computation 2014
DOI: 10.1145/2576768.2598338
|View full text |Cite
|
Sign up to set email alerts
|

Monotonic functions in EC

Abstract: To understand how evolutionary algorithms optimize the simple class of monotonic functions, Jansen (FOGA 2007) introduced the partially-ordered evolutionary algorithm (PO-EA) model and analyzed its runtime. The PO-EA is a pessimistic model of the true optimization process, hence performance guarantees for it immediately take over to the true optimization process.Based on the observation that Jansen's model leads to a process more pessimistic than what any monotonic function would, we extend his model by para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…Our positive result overlaps with the result of [29]. 2 He gives a sufficient condition for fast convergence that works in arbitrary dimensions: convergence is always fast if the matrix A has an eigenvector which contains only real, positive entries, and which has a corresponding positive real eigenvalue. In two dimensions with b, c < 0 and a, d > 0, we show in Lemma 2 that this is the case if and only if both eigenvalues of A are positive.…”
Section: Introductionsupporting
confidence: 57%
See 2 more Smart Citations
“…Our positive result overlaps with the result of [29]. 2 He gives a sufficient condition for fast convergence that works in arbitrary dimensions: convergence is always fast if the matrix A has an eigenvector which contains only real, positive entries, and which has a corresponding positive real eigenvalue. In two dimensions with b, c < 0 and a, d > 0, we show in Lemma 2 that this is the case if and only if both eigenvalues of A are positive.…”
Section: Introductionsupporting
confidence: 57%
“…In particular, the failure mode is not related to the trivial problems that occur for extremely large mutation rates, χ log n, where the algorithm fails to produce neighbors in Hamming distance one [32]. Subsequently, the results on how the mutation rate and related parameters affect optimization of monotone functions have been refined [2,20,24] and extended to a large collection of other EAs [18,26]. To highlight just one result, the (μ + 1)-EA with standard mutation rate 1/n fails on some monotone functions if the population size μ is too large (but still constant in n) [26].…”
Section: The Application: Twolinmentioning
confidence: 99%
See 1 more Smart Citation
“…Colin et al [5] have shown that PO-EA can be divided into two parts. Ma et al [6] have named it PO-mutation and ZeroMax models.…”
Section: Po-mutation Algorithmmentioning
confidence: 99%
“…The Partial Order Evolutionary Algorithm (PO-EA) model introduced by Jansen [3] contributes to the analysis of performance in linear functions and is expected to simulate the optimization of monotonic functions [4,5]. PO-EA is a pessimistic model of the true optimization process, which can be used to derive an upper bound on the expected hitting time of monotonic functions.…”
Section: Introductionmentioning
confidence: 99%